Responses of three nesting sea turtle species to hard-armoring structures - Hirsch, Sarah E.; Toonder, Madison; Reilly, Jennifer D.; Hoover, Shelby R.; Perrault, Justin R. (Frontiers in Marine Science, 2022)
In the face of modern challenges, analyzing sea turtle nesting trends is critical to better understand impacts to these vulnerable species. The introduction of hard-armoring structures (e.g., seawalls, rock revetments) on sea turtle nesting beaches poses a threat to nesting leatherback (Dermochelys coriacea), loggerhead (Caretta caretta), and green (Chelonia mydas) sea turtles due to habitat loss and turtle interactions with the physical structure. Despite much of Florida’s coastline being protected by some form of hard-armoring technology, research on the impacts of these structures to sea turtles is limited to loggerheads. Our objectives were to (1) examine nest density, nesting success, washout rates, and hatching and emergence success at hard-armoring sites in comparison to a control area and (2) characterize impacts of obstructions encountered by sea turtles nesting in northern Palm Beach County, Florida. Our results indicate that the hard-armoring site showed significantly lower nest density for green turtles and nesting success for loggerheads and green turtles in comparison to a control area. Additionally, nesting success for loggerheads and green turtles that encountered hard-armoring structures was significantly lower in comparison to those that encountered no obstructions or other obstructions (e.g., beach furniture, walkovers, escarpments, etc.). These results suggest that hard-armoring structures negatively impact sea turtle nesting behavior, which could result in loss of energy or other physiological derangements. Green turtles showed the most significant differences between the two sites, likely a result of their typical nest site selection favoring the upper portions of the beach, crawling further distances from the high-water line than loggerheads or leatherbacks. Before additional hard-armoring structures are permitted and installed, governing agencies should first consider more natural methods of protecting shorelines (e.g., dune restoration).